Islamic Green Contracts: Proposing an Islamic Financial Model to Support Agriculture Sector during Pandemic Covid-19 in Indonesia - HAMZAH, MUHAMMAD MAULANA; MIFTAH, AA; PANGIUK, AMBOK (International Journal of Islamic Economics and Governance, 2023)
The agriculture sector has shown numerous encouraging trends during a covid-19 outbreak in Indonesia. Despite its potential benefits, the application of Islamic finance products in this sector is limited. This research aims to propose a green Islamic financial model for supporting the agriculture sector. Library research and benchmark analysis are used to reveal the appropriate model. In the first step, the issues on financing in the agricultural sector will be overviewed. The second step will discuss the relevant theories to be adopted in this framework. The last part will propose the appropriate Islamic financial model. This research is limited to financing the crop sector of agriculture in Indonesia. This study finds that Islamic financing in the agricultural sector - is very diverse, such as Murabaha for the purchase of seeds or agricultural equipment, salam for sustainable farming, and istishna’ for land acquisition. The Islamic green financial model serves as guidance in synergizing strategy from various Islamic financial platforms to fulfill the needs of the agricultural sector and provides valuable analysis that combines classical theories and contemporary issues to draw the attention of Islamic financial practitioners to the fact that the needs of agriculture financial problems do not depend on single contract but needs to diversify the contract based on business process.